2007
DOI: 10.1111/j.1365-2648.2006.04091.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an osteoporosis prevention education programme for young adults

Abstract: Strategies used in this programme may provide guidance for the design of future programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
36
0
10

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 34 publications
6
36
0
10
Order By: Relevance
“…A professional nurse may be in the best position to offer this type of education [4&5]. In order to fulfill teaching roles, Nurses need adequate knowledge concerning osteoporosis, its etiology and risk factors, as well as preventative behaviors and also adequate osteoporosis health belief [6]. Studies about the prevalence of this disease in Kingdom of Saudi Arabia (KSA), has shown that among postmenopausal Saudi women 50-80 years of age, 39.5% has osteoporosis [7].…”
Section: Introductionmentioning
confidence: 99%
“…A professional nurse may be in the best position to offer this type of education [4&5]. In order to fulfill teaching roles, Nurses need adequate knowledge concerning osteoporosis, its etiology and risk factors, as well as preventative behaviors and also adequate osteoporosis health belief [6]. Studies about the prevalence of this disease in Kingdom of Saudi Arabia (KSA), has shown that among postmenopausal Saudi women 50-80 years of age, 39.5% has osteoporosis [7].…”
Section: Introductionmentioning
confidence: 99%
“…Les programmes d'éducation préventive de la stratégie OOS visent à agir sur certaines facettes du style de vie des adultes plus âgés, comme la prévention des chutes, les changements d'habitudes ali mentaires en raison d'affections concomi tantes, la diminution de l'apport alimentaire liée à l'âge, les interventions pharma cologiques et l'activité physique à faible impact 18 . Les jeunes adultes, définis ici comme étant âgés de 17 à 30 ans, période au cours de laquelle les habitudes alimen taires d'adulte et la masse osseuse se développent, ne sont pas touchés par cette information préventive, car leurs préoccu pations et leurs champs d'intérêt diffèrent de ceux des adultes plus âgés 9,19,20 . Les con traintes financières des organisations sans but lucratif, qui assurent la majeure partie de la tâche de diffusion de l'information, ont une influence sur la portée des pro grammes de sensibilisation sur l'ostéoporose : comme il est nécessaire de viser surtout les personnes les plus à risque, les jeunes adultes ne sont souvent pas pris en compte.…”
Section: Points Saillantsunclassified
“…1,2 The Surgeon General identified 10 million Americans over the age of 50 with osteoporosis, 34 million at risk, and predicted half of women over the age of 50 will have an osteoporotic fracture in their lifetime. 3 Reduced bone density can be the result of inadequate growth and/or excessive loss of bone tissue, all of which increase the likelihood of fracture.…”
Section: Introductionmentioning
confidence: 99%